Lattice Boltzmann Simulations of Thermocapillary Motion of Droplets in Microfluidic Channels (Communications in Computational Physics, 2018)
Our recently developed lattice Boltzmann model is used to simulate dropletdynamical behaviour governed by thermocapillary force in microchannels. One keyresearch challenge for developing droplet-based microfluidic systems is control ofdroplet motion and its dynamic behaviour. We numerically demonstrate that the thermocapillaryforce can be exploited for microdroplet manipulations including synchronisation,sorting, and splitting. This work indicates that the lattice Boltzmann methodprovides a promising design simulation tool for developing complex droplet-basedmicrofluidic devices.